Firm-sponsored apprenticeship training in Germany : empirical evidence from establishment data - Beckmann, Michael [Verfasser] (My University, 2002)
"This paper investigates the determinants of firm-sponsored apprenticeship training empirically using German firm-level data. The hypotheses for this study are based mostly on recent theoretical models about the financing of apprenticeship training which take labour market imperfections (e.g. mobility costs, asymmetric information, and wage floors) into account. Applying the usual probit, tobit, and trncated regression models, some empirical evidence is found supporting the relevance of active or passive poaching. Moreover, the results reveal some differences in the training behaviour of West and East German firms." (author's abstract, IAB-Doku) ((en))
Keywords: T 3.5 Statistik; T 3.4 Befragung; S 4.1 Finanzierungsquellen; T 4.6 Wirtschafts- und Rechtswissenschaften; IAB-Betriebspanel; Betriebliche Berufsausbildung; Einflussfaktor; Bildungsfinanzierung; Bildungsökonomie; Quantitative Angaben; 2000-2000